Critical functions in ensuring effective business continuity management. Evidence from Romanian companies - Păunescu, Carmen; Argatu, Ruxandra (Journal of Business Economics and Management, 2020)
The paper explores how business continuity management (BCM) is defined within the professional and academic communities that work in the field or research it. It sets out the framework for the composing elements of a BCM that emerge and considers how these various elements can interact with each other to build a sound business continuity management. Also, the paper aims to examine the organization’s critical functions that ensure an effective BCM. The research relies on a questionnaire-based survey, with data collected by personally interviewing top and middle-level managers from Romanian small and medium-sized companies. The results, which count on the responses of 119 participant companies, show that risk assessment takes a critical role in building the organization’s BCM strategy, while business continuity response planning has the strongest impact on the overall effectiveness of the organization’s BCM. The novelty of this research lies in a first time establishment of the critical functions that are vital for companies to maintain their essential business operations in case of disruptive incidents, to build organizational resilience. Future research should be grounded on testing if the BCM arrangements and business impact analysis influence the BCM strategy as the existing data did not prove that it did.